Effects of knowledge-translation anterior cruciate ligament injury prevention program on movement performance in youth female soccer players: A preliminary prospective study - Tzu-Chieh Liao; William H. Suits; Regina Marie Arriola; Nolan Fraaza; Jeongmin Hyun; Kenneth Conuel Oralde; Amanda O. Esquivel (Journal of Sports and Rehabilitation Sciences, 2025)
While anterior cruciate ligament (ACL) injury prevention programs (IPP) have shown strong evidence of their effectiveness, their implementation rate is low. Knowledge translation (KT) model is a proactive and evolving strategy designed to close the disconnect between proven research and practical application; therefore, this research aimed to examine the effectiveness of a KT-based ACL-IPP on the movement quality of young female soccer players. Eight female soccer players participated in a preliminary prospective study. The mean age, height, and weight of the participants were 13.3 (standard deviation [SD]=0.7) years old, 1.68 (SD=0.03) m, and 57.3 (SD=4.9) kg, respectively. The IPP was performed throughout a soccer season. Biomechanical analyses were performed before and following the IPP. Subjects were instrumented with motion capture markers and instructed to perform the following tasks: step down, drop jump, lateral shuffle, cutting, deceleration, and triple jump. Sagittal thigh angle, knee valgus angle, pelvic drop angle, and frontal trunk angle at maximum knee flexion were calculated. Paired t-tests were used to compare each movement performance in each task over time. The results revealed that sagittal thigh angle (mean difference=7.6 (SD=9.8)°, P=0.004) and knee varus (mean difference=3.5 (SD=5.8)°, P=0.014) were found to increase in drop jump. Sagittal thigh angle also increased in lateral shuffle (mean difference=2.1 (SD=4.8)°, P=0.047). However, pelvic drop angle was found to increase in deceleration (mean difference=2.6 (SD=3.7)°, P=0.006). The study demonstrated potential effectiveness of a KT-based ACL-IPP in showing improvement in shock absorption and knee stability among a group of youth female soccer players, both of which are critical in reducing risk of ACL injury. This preliminary prospective study provides a foundation for future research to explore the long-term benefits and feasibility of KT-based ACL-IPPs in a larger scale and diverse populations.